Equity crowdfunding sharia as Islamic social finance in recovering the economy amid covid-19 pandemic crisis in Indonesia - Friqly Aldinda (Department of Islamic Economic, Faculty of Economic and Business, Nahdlatul Ulama Islamic University (UNISNU) Jepara, Indonesia, 2022)
This research was conducted to elaborate on sharia equity crowdfunding as Islamic social finance that can be offered to deal with the Covid-19 pandemic in Indonesia. This study uses a descriptive qualitative approach with content analysis techniques and library research. The results of the study, it can be said that amid pandemic, sharia-based equity crowdfunding can be an option for businesses or can prevent this outbreak, especially SMEs, to maintain their business by getting assistance in terms of finance or resources because they maintain sharia principles that prioritizing justice and transparency to realize the benefit of people. Because sharia crowdfunding invests in halal products, shares the risk of its investment, and has a character that is free from interest and avoids: 1. Riba, which is an addition given in exchange for usury goods or additional agreed-upon principal debts. 2. Gharar, namely uncertainty in a contract both regarding the quality and quantity of the object of the contract. 3. Maysir, namely every contract that is carried out with unclear goals and inaccurate calculations, speculation, and chancy. 4. Tadlis, which is hiding the record of the object of the contract 5. Dharar, namely actions that cause harm or loss to other parties.